Second Derivatives

Calculus Level 3

y = 2 tan 1 ( 1 + x 2 1 x ) \large y = 2 \tan^{-1}\left(\frac{\sqrt{1+x^2}-1}{x}\right)

For y y as defined above, find d 2 y d x 2 \dfrac {d^2y}{dx^2} at x = 2 x = 2 .

4 25 \frac{4}{25} 4 25 \frac{-4}{25} 4 5 \frac{-4}{5} 2 36 \frac{2}{36}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Naren Bhandari
Feb 17, 2017

y = 2 t a n 1 ( 1 + x 2 1 x ) y = 2tan^{-1}(\frac{\sqrt{1+x^2} -1 }{x})

put x = t a n θ x = tan\theta

y = 2 t a n 1 ( 1 + t a n 2 θ 1 t a n θ ) y = 2tan^{-1}(\frac{\sqrt{1+ tan^2\theta} -1 }{tan\theta})

y = 2 t a n 1 ( s e c θ 1 t a n θ ) y = 2tan^{-1}(\frac{sec\theta -1}{tan\theta})

Since s e c θ = 1 c o s θ sec\theta = \frac{1}{cos\theta}

y = 2 t a n 1 ( 1 c o s θ t a n θ c o s θ ) y = 2tan^{-1}(\frac{1 - cos\theta}{tan\theta cos\theta})

y = 2 t a n 1 ( 2 s i n 2 θ 2 2 s i n θ 2 c o s θ 2 ) y = 2tan^{-1}(\frac{2sin^2\frac{\theta}{2}}{2sin\frac{\theta}{2} cos\frac{\theta}{2}})

y = 2 t a n 1 ( t a n θ 2 ) y = 2tan^{-1}(tan\frac{\theta}{2})

y = 2 θ 2 = > θ y = 2\frac{\theta}{2} => \theta

y = t a n 1 x y = tan^{-1}x

Differentiating with respect to x.

d y d x = 1 1 + x 2 \frac{dy}{dx} = \frac{1}{1+x^2}

Using the quotient rule for second derivatives

d y 2 d x 2 = 0 ( 1 + x 2 ) ( 2 x ) . 1 ( 1 + x 2 ) 2 \frac{dy^2}{dx^2} = \frac{0(1+x^2) - (2x).1}{(1+x^2)^2}

d 2 y d x 2 = 2 × 2 ( 1 + 2 2 ) 2 \frac{d^2y}{dx^2} = \frac{-2\times2}{(1+2^2)^2}

( d 2 y d x 2 ) ( x = 2 ) = 4 25 (\frac{d^2y}{dx^2})_(x=2) = \boxed{\frac{-4}{25}}

Chew-Seong Cheong
Feb 17, 2017

y = 2 tan 1 ( 1 + x 2 1 x ) tan y 2 = 1 + x 2 1 x Let x = tan θ = sec θ 1 tan θ Multiply up and down by cos θ = 1 cos θ sin θ Let t = tan θ 2 = 1 1 t 2 1 + t 2 2 t 1 + t 2 = 1 + t 2 1 + t 2 2 t = t = tan θ 2 \begin{aligned} y & = 2 \tan^{-1} \left(\frac {\sqrt{1+x^2}-1}x\right) \\ \tan \frac y2 & = \frac {\sqrt{1+x^2}-1}x & \small \color{#3D99F6} \text{Let } x = \tan \theta \\ & = \frac {\sec \theta - 1}{\tan \theta} & \small \color{#3D99F6} \text{Multiply up and down by } \cos \theta \\ & = \frac {1 - \cos \theta}{\sin \theta} & \small \color{#3D99F6} \text{Let } t = \tan \frac \theta 2 \\ & = \frac {1 - \frac {1-t^2}{1+t^2}}{\frac {2t}{1+t^2}} \\ & = \frac {1+t^2-1+t^2}{2t} \\ & = t = \tan \frac \theta 2 \end{aligned}

y = θ tan y = x Differentiate both sides w.r.t x sec 2 y d y d x = 1 d y d x = cos 2 y d 2 y d x 2 = 2 cos y sin y d y d x = 2 cos 3 y sin y d 2 y d x 2 x = 2 = 2 ( 1 5 ) 3 ( 2 5 ) tan y = x = 2 = 4 25 sin y = 2 5 , cos y = 1 5 \begin{aligned} \implies y & = \theta \\ \tan y & = x & \small \color{#3D99F6} \text{Differentiate both sides w.r.t } x \\ \sec^2 y \cdot \frac {dy}{dx} & = 1 \\ \frac {dy}{dx} & = \cos^2 y \\ \frac {d^2y}{dx^2} & = - 2 \cos y \sin y \cdot \frac {dy}{dx} \\ & = - 2 \cos^3 y \sin y \\ \frac {d^2y}{dx^2} \bigg|_{x=2} & = - 2 \left(\frac 1{\sqrt 5}\right)^3 \left(\frac 2{\sqrt 5}\right) & \small \color{#3D99F6} \tan y = x = 2 \\ & = \boxed{-\dfrac 4{25}} & \small \color{#3D99F6} \implies \sin y = \frac 2{\sqrt 5}, \ \cos y = \frac 1{\sqrt 5} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...